EVALUATION OF NUTRITIONAL STATUS IN PERITONEAL DIALYSIS (PD) PATIENTS - Max Dratwa; Christian Verger (The Korean Society of Nephrology, 2012)
In 2009, analysis of the French Language Peritoneal Dialysis Registry (RDPLF) data revealed that 6 patients out of 355 (1,7%) were transferred to HD because of malnutrition after a median period of 31 months. Furthermore, malnutrition was responsible for the death of 5.1 % patients after a median period of 14 months. So, as nutritional status has been shown to impact morbidity and mortality of dialysis patients, we set out to measure this status in incident PD patients of 2 European centers using various validated methods. The techniques used were: anthropometric,BMI and biochemical measurements, SGA, Brandes score, total (renal and peritoneal) creatinine excretion, dietician records, handgrip strength, DEXA, multifrequency electrical bioimpedance (TBIA). Daily dietary protein intake was less than 1g/kg ideal BW in 35 % of pts while 38% ate more than 1.2 g/kg; daily total (oral and peritoneal) caloric intake was 28±8 kcal/kg. Fifteen % of patients (median age 71) had a very low serum albumin level (<30 g/l) while 50 % maintained their albumins > 50 g/l (median age 64 years). Very significant correlations were found between: 1) estimation of fat mass by skinfold thickness and that modelised from the water volume determined by TBIA (r²: 0.56, p<0.0001); 2) brachial circumference and lean body mass determined by TBIA (but no correlation between middle arm circumference and handgrip strength) ; 3) muscle mass determined by creatinine kinetics and TBIA (r²: 0.68, p<0.001); 4) muscle mass estimated by brachial circumference and lean body mass estimated through creatinine kinetics; 5) handgrip strength and lean body mass determined both by TBIA and by creatinine kinetics (r²: 0.59, p<0.0001); 6) lean body mass and age (but different between males and females); 7) protein losses in the dialysate and lean body mass derived from creatinine kinetics. In conclusion, malnutrition is more threatening as patients age. Patients with a low initial lean body mass and low protein intakes should be closely monitored such as protein losses do not counterbalance the theoretical advantages of a higher dialysis dose.